2008
DOI: 10.1363/3412108
|View full text |Cite
|
Sign up to set email alerts
|

Does Community Clustering Mitigate the Negative Effect of Poverty on Adolescent Condom Use in South Africa?

Abstract: Young women in South Africa face an especially daunting transition into adulthood. At the current rate of infection, one in every three will be HIV-positive by age 21. 1 A 2005 nationally representative HIV prevalence study among 15-24-year-olds in South Africa documented an abrupt rise in HIV prevalence among young women: Although only 4% of women 15-19 were HIV-positive, more than one-third of women were infected by age 21. 2 A study conducted in 2000 among university students in KwaZuluNatal-the site of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…1 Intra-uterine devices (IUDs) can be used without replacement for up to 5 years; however, many women associated infertility with IUD use and thus were hesitant to use that method. 74 Indeed, reasons for not using certain methods of contraceptives varied highly based on the availability of the method at local health facilities as well as the ease of use and replacing the device(s).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Intra-uterine devices (IUDs) can be used without replacement for up to 5 years; however, many women associated infertility with IUD use and thus were hesitant to use that method. 74 Indeed, reasons for not using certain methods of contraceptives varied highly based on the availability of the method at local health facilities as well as the ease of use and replacing the device(s).…”
Section: Resultsmentioning
confidence: 99%
“…20 Furthermore, even though some contraceptives such as IUDs are more cost-effective in the long-term, the up-front cost of the device is a deterrent for some individuals. 74 It is important to note, however, that in some sub-Saharan African countries, contraceptives such as the pill, injectables, or condoms can be obtained free of cost through the county’s ministry of health. 74 Although this varies by country, and even within countries, for women without access to subsided contraception, cost can be a tremendous barrier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding might be due to the free or subsidised CPs offered to clients in some African countries, and is likely to close the differences in the cost of obtaining a CP between clients with and without a health insurance. [47][48][49] Our null finding on the association between perceived domestic violence and modern CP use is unique. To the best of our knowledge, there has not been a large population-based study in the African context that has examined the influence of perceived domestic violence on modern CP use among women of reproductive age, though studies on domestic violence on CPs use more generally have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Research found that contraceptive use in low-income countries increases with the share of government facilities that tend to provide services with low cost or no cost 39. While long-acting reversible methods are cost-effective in the long term, it can be challenging for individuals to pay the upfront cost of the services 40. Although in Haiti public health facilities are mandated to provide free family planning service, cost could still be a barrier to contraceptive use when women have to use the private sector due to the lack or stock-out of methods in public facilities 41.…”
Section: Discussionmentioning
confidence: 99%